2022
DOI: 10.1021/acsaem.2c02254
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen Bubble-Assisted One-Step Electrodeposition of Cu, Ni, and P toward Electrocatalytic Water Oxidation

Abstract: Development of low-cost and highly abundant transition metal-based electrocatalysts for oxygen evolution reaction (OER) activity with low overpotential and high stability is desired for the utilization of electrolytic water-splitting cells to generate hydrogen (H2) fuel. The electrocatalytic activity could be further improved with the fabricated catalyst possessing microporous structures. In this study, binder-free hydrogen bubble-assisted electrodeposition of Cu, Ni, and phosphorous over a Cu sheet (CuNiP@Cu … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 59 publications
0
6
0
Order By: Relevance
“…It is very important to prepare OER catalytic electrodes with high efficiency and low cost for hydrogen production from water electrolysis. 4,5 Siwal et al 6 introduced the OER mechanism of electrolyzed water at the anode to produce oxygen and discussed the research progress of nonprecious metal active materials. Li et al 7 suggested that the transition metal electrode showed significant activity in catalytic performance and could be used as a substitute for noble metal catalytic electrodes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is very important to prepare OER catalytic electrodes with high efficiency and low cost for hydrogen production from water electrolysis. 4,5 Siwal et al 6 introduced the OER mechanism of electrolyzed water at the anode to produce oxygen and discussed the research progress of nonprecious metal active materials. Li et al 7 suggested that the transition metal electrode showed significant activity in catalytic performance and could be used as a substitute for noble metal catalytic electrodes.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the development and utilization of low-cost, highly active, and stable electrocatalysts have become a hot research field. It is very important to prepare OER catalytic electrodes with high efficiency and low cost for hydrogen production from water electrolysis. , …”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, the formation of phosphate can act as a ligand to facilitate the conversion from lowvalent to high-valent Co in the redox reaction and promote the four-electron proton coupling transfer steps during the OER, thereby enhancing the activity of the OER. 56 The electrocatalytic performances of the as-prepared samples were investigated in a 1 M KOH solution with typical three-electrode systems. Linear sweep voltammetry (LSV) is used to investigate the electrocatalytic activity of materials for OER.…”
Section: Resultsmentioning
confidence: 99%
“…13 However, this electrocatalyst showed low activity toward the HER and OER and required high overpotential to reach even low current densities (at least ∼−130 mV for HER and ∼300 mV for OER at 10 mA cm −2 ) compared to noble-based catalysts. 10,14,15 Consequently, it needs further improvement. It should be noted that CuNiP UOR activity has not been reported yet.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, it has been determined that adding Cu can boost Ni 3+ ions, which is considered an active catalytic site for OER and UOR reactions, and increase the corrosion resistance of the electrode . However, this electrocatalyst showed low activity toward the HER and OER and required high overpotential to reach even low current densities (at least ∼−130 mV for HER and ∼300 mV for OER at 10 mA cm –2 ) compared to noble-based catalysts. ,, Consequently, it needs further improvement. It should be noted that CuNiP UOR activity has not been reported yet.…”
Section: Introductionmentioning
confidence: 99%